Effectivity of PCR and AGID methods to detect of enzootic bovine leukosis in Indonesia - Saepulloh M; Sendow I (Indonesian Center for Animal Research and Development (ICARD), 2015)
Enzootic Bovine Leucosis (EBL) is one of viral diseases in cattle caused by bovine leukemia virus (BLV), from Retroviridae. The virus can be detected using severals methods such as Polymerase Chain Reaction (PCR), while antibody can be detected using Agar Gel Immunodifussion (AGID). The aim of this experiment was to study the effectivity of PCR and AGID methods to detect enzootic bovine leukosis virus in Indonesia. Samples of peripheral blood leukocyte (PBL) were collected from cattles those with and without showing clinical signs. A total of 307 blood and serum samples were tested against BLV using PCR and AGID tests, while 21 semen samples which were from similar animals for blood collection were collected only for PCR test. The results indicated that twelve cattles have positive results with PCR test in PBL, but from those cattles only seven were positive with AGID. On the other hand, the PCR did not detect EBL in 21 bovine semen samples tested, although one sample gave positive result with PCR in PBL. This results indicated that PCR method from blood samples was more sensitive than that AGID method. The PCR detection was also more sensitive for PBL than that for semen samples.